Cyber Honeypot (International Journal of Scientific Research in Science and Technology, 2024)
In an era of escalating cyber threats, the need for robust defenses against malicious activities is paramount. In this project, we propose a novel approach to leverage honeypots in conju nction with Canary Tokens to accurately pinpoint the geographical locations of attackers. By strategically deploying these decoy resources across diverse network environments, we capture valuable data on unauthorized access attempts and malicious behavior. Through the analysis of Canary Tokens, which act as unique identifiers triggered upon interaction, we can trace the origin of these attacks to specific IP addresses. Utilizing this information, security professionals gain insights into the geographical distribution of attackers, aiding in threat intelligence, incident response, and the implementation of targeted security measures. This integration of project honeypots and Canary Tokens enhances network defense strategies, providing organizations with a proactive stance against cyber threats.